2004
DOI: 10.1364/opex.12.004246
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical angle fluorescence (SAF) microscopy

Abstract: We explore a new confocal microscope for the detection of surface-generated fluorescence. The instrument is designed for high resolution imaging as well as for the readout of large biochips. Special feature is the separated collection of two different fluorescence emission modes. One optical path covers the emission into the glass at low surface angles, the other captures high angles, exceeding the critical angle of the water/glass interface. Due to the collection of the supercritical angle fluorescence (SAF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 0 publications
2
94
0
Order By: Relevance
“…The optical set-up is inverse to that of TIRF with an excitation beam illuminating the sample perpendicularly and a collection of fluorescence light emitted into the supercritical angle of the substrate using a parabolic mirror objective. The SAF technology itself (2000) [238,239], a SAF sensing instrument (2003) [240], and also a SAF imaging instrument (2007) [241,242] were recently developed. The strength of the SAF technique to study protein adsorption phenomena was demonstrated in some recent publications [44,102,118,187] or TIRF set-ups and, more recently, also with the SAF optics [244].…”
Section: Fluorescence Detection Techniquesmentioning
confidence: 99%
“…The optical set-up is inverse to that of TIRF with an excitation beam illuminating the sample perpendicularly and a collection of fluorescence light emitted into the supercritical angle of the substrate using a parabolic mirror objective. The SAF technology itself (2000) [238,239], a SAF sensing instrument (2003) [240], and also a SAF imaging instrument (2007) [241,242] were recently developed. The strength of the SAF technique to study protein adsorption phenomena was demonstrated in some recent publications [44,102,118,187] or TIRF set-ups and, more recently, also with the SAF optics [244].…”
Section: Fluorescence Detection Techniquesmentioning
confidence: 99%
“…This is commonly achieved by an evanescent illumination of the sample by TIR of the excitation light at the cover slip-sample interface [15]. TIR fluorescence microscopy (TIRFM) is receiving much attention, both because of its simple implementation using either lenses of high numerical aperture or prism-based illumination, and its exceptional performance with respect to the contrast of the imaged structures at the interface versus structures in the volume (see for example [16][17][18][19][20][21][22][23]). TIRFM only detects the fluorophores near the cover glass-sample interface because of the finite penetration depth of the evanescent excitation field of typically <100 nm.…”
Section: Introductionmentioning
confidence: 99%
“…at the interface. Introduced either with a scanning approach [4] or with full-field imaging [5,6] the same axial resolution as TIRF can be obtained. Although fluorescence is a useful tool for biological study, this technique suffers from limitations.…”
Section: Biophotonicsmentioning
confidence: 99%